2013
DOI: 10.1111/and.12109
|View full text |Cite
|
Sign up to set email alerts
|

A minimum number of motile spermatozoa are required for successful fertilisation through artificial intrauterine insemination with husband's spermatozoa

Abstract: Intrauterine insemination (IUI) is an effective, noninvasive, relatively simple and cheap method of infertility treatment. Many factors that affect IUI outcomes have been studied. However, there is no consensus about the optimal number of motile spermatozoa inseminated (NMSI) required for a reasonable chance of pregnancy after IUI. In this retrospective study, we aimed to assess the relationship between NMSI and the pregnancy rate after IUI with husband's spermatozoa. Couples who had either primary or secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…It has been shown that pregnancy rates may vary significantly depending on the number of motile sperm inseminated ( Badawy et al. , 2009 ; Merviel et al , 2010 ; Cao et al , 2014 ). Dinelli et al (2014) reported that the main problem related to male infertility was moderated asthenozoospermia, and that pregnancy rates were significantly higher when the number of motile sperm with progressive motility used in insemination was at least 1×10 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pregnancy rates may vary significantly depending on the number of motile sperm inseminated ( Badawy et al. , 2009 ; Merviel et al , 2010 ; Cao et al , 2014 ). Dinelli et al (2014) reported that the main problem related to male infertility was moderated asthenozoospermia, and that pregnancy rates were significantly higher when the number of motile sperm with progressive motility used in insemination was at least 1×10 6 .…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that only a sperm presence with +4 motility increased clinical pregnancy rates, which might be explained due to this study only including an unexplained and mild male subfertile patient group. Cao et al (35) evaluated 1153 IUI cycles in 2014 and reported that a number of motile sperms lower than 2×10 6 in the insemination had low success rates in IUI, but the author also showed that sperm numbers higher than this is increased the observed pregnancy rates. They concluded that IUI can be performed when the NMSI (number of motile sperm inseminated) exceeds 2x10 6 .…”
Section: Discussionmentioning
confidence: 99%
“…As regard to swim-up and density gradient centrifugation, the differences in the number of either technique used (128 swim-up vs. 725 DGC) can be explained by the fact that after the publication of Morshredi et al [31] in 2004 indicating that "although samples with an acceptable number of motile sperm can be processed efficiently by wash only, poor quality semen samples should be processed using DGC", we decided that sperm would be prepared exclusively by DGC. The fact that the threshold for IUI we determined is relatively higher than that proposed by Dinelli et al [11] and Cao et al [32] is probably due to the fact that we did not include the couples with extremely poor sperm in the study; those couples being treated by ICSI. The big limitation of our study is its retrospective nature.…”
Section: Discussionmentioning
confidence: 62%